Convergence of frontline nutrition and health workers in tribal communities of Maharashtra: a cross-sectional mixed-methods study - Sinha, Shelley S.; Sanyal, Subhashree (International Journal Of Community Medicine And Public Health, 2025)
Background: In India, despite decades of targeted nutrition and health programmes, progress on child malnutrition has been uneven and fragmented. Achieving sustained improvements in malnutrition requires multi-sectoral convergence at all levels. Institutionalizing convergence between ICDS and health sectors is essential to amplify the impact. POSHAN Abhiyan launched in 2018 was a landmark step towards institutionalizing convergence and amplified shared platforms like VHSND and joint collaboration between frontline workers. Methods: This mixed-method study was conducted from November 2023 to October 2024 in two tribal dominated blocks in two districts of Maharashtra. A structured questionnaire was used to collect information about the convergence role and mechanisms among FLWs of ICDS and health department from AWWs. Focus group discussions with ASHAs and in-depth interviews with ANMs, were also conducted to understand their role and perspective on convergence between ICDS and health at the village level. Results: Findings show the VHSND platform is routinely convened and often meets duration norms, with effective case-based collaboration for referral and high-risk follow-up. However, structured joint counselling is infrequent, joint training and supervisory visits are rare. Community governance mechanisms like VHNSCs remain largely inactive and uneven micro planning undermine service quality of nutritional interventions. Conclusions: Policy and program actions should prioritize enforcing joint-cadre, counselling of service users and effective micro planning going beyond practical issues, institutionalizing routine cross-sector training and supervision and reactivating local governance for accountability to sustain nutrition services among marginalized communities.